2017
DOI: 10.1186/s12882-017-0593-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity, capacity and nutritional status in elderly peritoneal dialysis patients

Abstract: BackgroundThis study aimed to evaluate the prevalence of sedentarism, and to assess physical capacity and nutritional status in a cohort of older patients on peritoneal dialysis (PD), with respect to age-matched non-dialysis CKD population, using highly accessible, simple methods, namely the Rapid Assessment of Physical activity (RAPA) test and the 30″ Sit-to-stand (STS) test.MethodsThis cross-sectional multicenter study included 151 renal patients older than 60 years; 71 pts. (44 m, age 72 ± 7 yrs) were on PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Lack of knowledge regarding benefits of exercise among people being treated with PD was also a finding in this study and was associated with age as an exercise barrier. Older age is associated with low level of physical activity and declined exercise capacity in CKD, HD and PD populations (Zuo et al 2013; Cobo et al 2015; Cupisti et al 2017). Given that education regarding exercise is not part of routine practice in dialysis care (Bennett et al 2017), it is likely that people treated with PD, especially those of older age, may lack knowledge regarding appropriate exercise regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of knowledge regarding benefits of exercise among people being treated with PD was also a finding in this study and was associated with age as an exercise barrier. Older age is associated with low level of physical activity and declined exercise capacity in CKD, HD and PD populations (Zuo et al 2013; Cobo et al 2015; Cupisti et al 2017). Given that education regarding exercise is not part of routine practice in dialysis care (Bennett et al 2017), it is likely that people treated with PD, especially those of older age, may lack knowledge regarding appropriate exercise regimens.…”
Section: Discussionmentioning
confidence: 99%
“…People with ESKD receiving PD experience low activity levels (Painter et al 2017). These low activity levels are a result of chronic fatigue (Bonner et al 2010; Painter et al 2017), poor nutritional status (Zuo et al 2013; Cupisti et al 2017), co‐morbidities (Kang et al 2017; Painter et al 2017), older age (Bonner et al 2010; Zuo et al 2013) and the burden of dialysis treatment time (Oishi et al 2012). Physical inactivity can lead to significant weight gain, muscle wasting and an increased risk of other comorbidities such as cardiovascular disease, anxiety and depression (Finlay & Mark 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…16 Furthermore, frailty and sarcopenia can lead to fracture, hospitalization, and death. The association between muscle strength, inflammation, and mortality and poor physical function in dialysis patients 17 suggests this is a significant issue for people receiving PD.…”
Section: Pd Patients Are S Edentarymentioning
confidence: 99%
“…Another study reported a high prevalence of low-performance capacity among elderly patients treated with PD. Interestingly, performance level of PD patients did not appear to differ from the cohort of non-dialysis CKD patients [48]. Objectively measured physical function and ability to perform activities of daily living and self-care have been reported to be reduced across the CKD-Dialysis-Transplant spectrum [49].…”
Section: Counteracting the Caloric Load From Glucose Absorption: An Ementioning
confidence: 92%